Nursing care for kindney cancer: an experience report (Research, Society and Development, 2022)
Objective: To describe nursing care provided to kidney cancer and its postoperative complications. Methodology: This is a descriptive study, of the type of experience report that was developed from 09th to 24th of august 2021, in the urology clinic of a reference hospital in oncology in the state of Pará, referring to a nursing care in those affected by kidney cancer that evolved with postoperative complications. Result and discussion: The developmente of the expeience occurred in the postoperative period and from the evolution of the clinical picture of the disease, a care plan was elaborated for possible postoperative complications in nephrectomy. The diagnoses were elaborated based on the Taxonomia II from NANDA-I, was used in version 2018-2020 and the interventions proposed based on the Classification of Nursing Interventions – NIC version 2016. Conclusion: Nursing care of the oncology requires care based on technical and scientific knowledge, especially in the face of possible complications involving physical, physiological, pychological, social and spiritual aspects. In this sense, it is essencial that the nursing team has the skills to promote quality, humanized and holistic care, aiming to reduce the adverse effects of the treatment.